PEMBELAJARAN SASTRA BERBASIS KARAKTER - Endang Waryanti (Universitas PGRI Adi Buana Surabaya, 2015)
Abstract Learning can be characterized through various mediation. One of mediation that through literature. In the literature there is idol, exemplary character reader. From this idol may be withdrawn character. In addition, in the literature there is a message or mandate. Through the mandate of readers also get a character study. From both sides, reading literature means reading the character the next process in the reader there will be a process of internalization cultivation of character values. In that regard, although the literature is seen as a projection of life that may be characters, setting, conflict is all around us. Thus, literature as the embodiment of life will provide inspiration for the reader to ponder and further will be an example for him. Key Word: instructional literature, the values of character, literary contribution in the formation of character, character planting strategy.